A simple non-equilibrium, statistical-physics toy model of thin-film growth. (16th September 2015) - Ochab, Jeremi K; Nagel, Hannes; Janke, Wolfhard; Waclaw, Bartlomiej
Abstract: We present a simple non-equilibrium model of mass condensation with Lennard–Jones interactions between particles and the substrate. We show that when some number of particles is deposited onto the surface and the system is left to equilibrate, particles condense into an island if the density of particles becomes higher than some critical density. We illustrate this with numerically obtained phase diagrams for three-dimensional systems. We also solve a two-dimensional counterpart of this model analytically and show that not only the phase diagram but also the shape of the cross-sections of three-dimensional condensates qualitatively matches the two-dimensional predictions. Lastly, we show that when particles are being deposited with a constant rate, the system has two phases: a single condensate for low deposition rates, and multiple condensates for fast deposition. The behaviour of our model is thus similar to that of thin film growth processes, and in particular to Stranski–Krastanov growth.